Can transcranial magnetic stimulation (TMS) facilitate language recovery in chronic global aphasia post-stroke? Evidence from a case study - Georgiou, Anastasios M.; Phinikettos, Ioannis; Giasafaki, Chrysa; Kambanaros, Maria (My University, 2020)
The present study reports the findings of a 10-consecutive day neuronavigated continuous theta burst stimulation (cTBS) treatment over the right pars triangularis (pTr) for one individual with chronic global aphasia post-stroke. Baseline language and quality of life measures were collected twice prior to treatment, one day post-treatment, and then at two and 12-months follow up. Therapy was tolerated well by A.M. and no side effects were noticed during and after treatment. Results showed a trend towards improvement in expressive language in the short-term (i.e. one day post-treatment), significant improvement in spoken comprehension and moderate improvement in reading performance at follow-up (i.e. two months and one year post-treatment). Quality of life (QoL) did not significantly change as a result of the treatment. Findings from this study indicate that cTBS over the right pTr has the potential to induce recovery of aphasia across various language skills. Further research exploring individualized TMS protocols for aphasia rehabilitation post-stroke is strongly suggested with the goal that TMS can be used as a treatment modality for aphasia post-stroke in the near future.
Keywords: Transcranial magnetic stimulation (TMS); Theta burst stimulation (TBS); Neuronavigation; Quality of life; Case-based approach